Jira 8 administration cookbook : over 80 recipes to administer, customize, and extend Jira Core and Jira Service Desk /: over 80 recipes to administer, customize, and extend Jira Core and Jira Service Desk. (2019) - Li, Patrick, 1983-
No abstract available